Computer-based learning application to teach introduction to multimedia for university students - Kong, Xue Ying (2019)
The expected output of this proposed project is a computer-based learning application which will be able to support interactivity with user in learning process. It targeted to be exposed to university students as an alternative of conventional lecture presentation slides or other paper-based learning materials for the purpose of teaching a subject that offered in Faculty of Information Communication and Technology, Universiti Tunku Abdul Rahman (UTAR), which is “Introduction to Multimedia”. It aims to introduce the fundamentals of multimedia elements and tools for the students. The ADDIE model of instructional design was used to help develop the application. The course will be pre-setting up into the computer application by integrating all learning materials and quiz with answers provided. Besides, the course content was designed with multiple choice of delivery formats such as interactive slides and video. Interactive slides means adding more interactive features into the conventional presentation slides, for example, buttons allocated in each slide to allow non-linear flow of content. Meanwhile, video helps to catch user’s eye in teaching certain content like theory-based topics because it is demonstration-friendly. In addition, the attractiveness of the application can be enhanced by adding graphics, audio and animations so that it could grab the user’s attention easily. The proposed application does not require Internet and browser to support its operation, mostly shared via external storage devices such as DVD or CD and thumb drive.